Aksi Terorisme: Dari Gerakan Ideologis ke Gerakan Inkostitusional - Suprapto Suprapto (Sociology Department Of Syiah Kuala University, 2018)
Terrorism has caused unrest at both national and global levels. The terrorist movement triggered conflicts caused disintegration until unconstitutional action. Based on these conditions, this paper explains: 1) the terrorism movement on an ideological basis, 2) the terrorist movement in unconstitutional efforts towards the destination country. As for ideological movements, terrorism has two types, namely; state terrorism and non-state terrorism. ISIS, which is classified as state terrorism, has hegemonized many countries, groups, and even released cadres to several countries. According to the sociological literature, terrorists and counter-terrorists originating from the politics of science, international studies, and law. While in an unconstitutional movement, terrorism has an agenda to bring up state conflicts.Keywords: Terrorism, Ideological Movement, Unconstitutional Movement Terorisme telah menimbulkan keresahan baik di tingkat nasional maupun global. Gerakan terorisme juga memicu konflik yang menyebabkan disintegrasi sampai tindakan inkonstitusional. Berdasarkan kondisi tersebut, tulisan ini menjelaskan tentang: 1) gerakan terorisme dengan basis ideologis, 2) gerakan terorisme dalam upaya-upaya inkonstitusional terhadap negara. Adapun gerakan ideologis, terorisme memiliki dua jenis, yakni; state terorism dan non-state terorism. ISIS yang tergolong state terorism, telah banyak menghegemoni negara, kelompok, hingga pelepasan kader ke beberapa negara. Sesuai literatur sosiologis, teroris dan kontra teroris berawal dari politik sains, studi internasional, dan hukum. Sedang dalam gerakan inkonstitusional, terorisme memiliki agenda untuk memunculkan konflik kenegaraan. Kata Kunci: Terorisme, Gerakan Ideologis, Gerakan Inkonstitusional